Simultaneous N, C, S stable isotope analyses using a new purge and trap elemental analyzer and an isotope ratio mass spectrometer. (29th October 2014) - Fourel, François; Martineau, François; Seris, Magali; Lécuyer, Christophe
<x xml:space="preserve">Abstract</x> RATIONALE The evolution of stable isotope applications has demonstrated the increasing need for the determination of more than one isotopic signature from the same sample. Simultaneous determinations of 13C/12C and 15 N/14 N have become a widespread technique but up to now very few fully automated systems have offered the possibility of also measuring 34S/32S from the same sample aliquot. This could be critical when sample amounts are limited, but it could also represent a significant gain of analytical time or cost. The technique that we are presenting provides these multiple isotopic signatures on small sample aliquots with high precisions, especially for sulfur determinations. METHODS A high‐precision, easy and rapid method for the simultaneous measurement of carbon (13C/12C), nitrogen (15 N/14 N) and sulfur (34S/32S) ratios as well as elemental concentrations was employed, using a new combination of an elemental analyzer and an isotope ratio mass spectrometer. The elemental analyzer was based on 'purge and trap' technology rather than conventional packed‐gas chromatography (GC) gas separation. Emphasis was put on the efficiency of the system to reliably combust sulfur‐bearing compounds of both organic and inorganic origin with high conversion yields. RESULTS High‐quality measurement of 34S/32S ratios was obtained using various international reference materials. A working calibrated material was also selected and characterized for all three isotopic signatures in order to fully use the capacities of the system in future work. CONCLUSIONS The possibilities of such a system for the reliable measurement of S isotope ratios as well as N and C isotope ratios within the same aliquot of sample opens up new fields of investigation in many domains where multi‐isotopic approaches are required. Copyright © 2014 John Wiley & Sons, Ltd.